Advances in Experimental Medicine and Biology
DOI: 10.1007/0-306-46832-8_16
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stat3 in Apoptosis and Mammary Gland Involution

Abstract: STATs (signal transducer and activator of transcription) are a family of latent transcription factors which are activated in response to a variety of cytokines and growth factors. This family of signalling molecules have been implicated in growth, differentiation, survival and apoptosis. In this article, we will review work which highlights the role of individual STAT factors in mammary gland and demonstrate the value of genetically modified mice in defining the function of STAT3. Involution of the mouse mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
1

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 26 publications
4
86
0
1
Order By: Relevance
“…It is possible that stage of progression through the cell cycle, or other transcription factors such as signal transducer and activator of transcription 3 (STAT3), may be involved. STAT3 has been implicated in apoptosis (Akira, 2000;Chapman et al, 2000), and CD40 ligation in B cells results in tyrosine phosphorylation of Janus tyrosine kinase3, leading to the phosphorylation and subsequent activation of STAT3 (Hanissian and Geha, 1997). We have previously reported NF-B and AP-1 activation in response to CD40 ligation in primary human cholangiocytes (Afford et al, 2001), and further experiments have confirmed that both hepatocytes and cholangiocytes show similar signaling responses to CD40 activation (our unpublished data for cholangiocytes).…”
Section: Discussionsupporting
confidence: 59%
“…It is possible that stage of progression through the cell cycle, or other transcription factors such as signal transducer and activator of transcription 3 (STAT3), may be involved. STAT3 has been implicated in apoptosis (Akira, 2000;Chapman et al, 2000), and CD40 ligation in B cells results in tyrosine phosphorylation of Janus tyrosine kinase3, leading to the phosphorylation and subsequent activation of STAT3 (Hanissian and Geha, 1997). We have previously reported NF-B and AP-1 activation in response to CD40 ligation in primary human cholangiocytes (Afford et al, 2001), and further experiments have confirmed that both hepatocytes and cholangiocytes show similar signaling responses to CD40 activation (our unpublished data for cholangiocytes).…”
Section: Discussionsupporting
confidence: 59%
“…MMTV-AKT1 mice universally exhibited varying degrees of delayed involution, which coincided with elevated cyclin D1 levels, increased AKT1 activation and an increased number of mitotic cells (Figures 5 and 7). The delay in involution correlated with the persistence of phospho-Tyr705-STAT3, which disappeared upon involution (Li et al, 1997;Chapman et al, 1999). There was a direct correlation between prolonged expression of activated AKT and cyclin D1 in the involuting mammary gland of both founder lines (Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 83%
“…The induction of involution in the mammary gland is accompanied by a strong P-STAT3 activation and results in the massive apoptosis of alveoli. Sumoylation results in an increased protein stability and possibly points at a role for PIAS3 to limit P-STAT3 activity at the end of the involution process (33). From these data, it is tempting to speculate that PIAS3 protects normal cells from P-STAT3 addiction by fine tuning P-STAT3 activity and preventing its oncogenic effects.…”
Section: Discussionmentioning
confidence: 99%